2014
DOI: 10.1101/002006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide patterns of copy number variation in the diversified chicken genomes using next-generation sequencing

Abstract: Background: Copy number variation (CNV) is important and widespread in the genome, and is a major cause of disease and phenotypic diversity. Herein, we performed a genome-wide CNV analysis in 12 diversified chicken genomes based on whole genome sequencing. Results: A total of 8,840 CNV regions (CNVRs) covering 98.2 Mb and representing 9.4% of the chicken genome were identified, ranging in size from 1.1 to 268.8 kb with an average of 11.1 kb. Sequencing-based predictions were confirmed at a high validation rate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 76 publications
6
39
0
1
Order By: Relevance
“…Due to its economic and agricultural importance, the wild progenitor of the Domestic Chicken, Gallus gallus (Red Junglefowl), was the first avian species whose genome was completely sequenced (ICGSC 2004). Since then, genomes of many of the hundreds of different breeds of Gallus gallus have been sequenced (e.g., Imsland et al 2012;Yi et al 2014;Wang et al 2015;Lawal et al 2018;Li et al 2019;Yang et al 2019), resulting in a large number of available chicken genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its economic and agricultural importance, the wild progenitor of the Domestic Chicken, Gallus gallus (Red Junglefowl), was the first avian species whose genome was completely sequenced (ICGSC 2004). Since then, genomes of many of the hundreds of different breeds of Gallus gallus have been sequenced (e.g., Imsland et al 2012;Yi et al 2014;Wang et al 2015;Lawal et al 2018;Li et al 2019;Yang et al 2019), resulting in a large number of available chicken genomes.…”
Section: Introductionmentioning
confidence: 99%
“…근래에는 chicken genome sequencing 결과를 토대로 개발된 HD-SNP chip 데이터를 이용하여 다형성이 높고, 품종 특이성을 가진 마커를 선발하여 품종 구분에 이용하는 방법이 개발되기도 하였으며, 이 방법의 경우 전 자동화된 분석 기술과 낮아지고 있는 분석비용으로 MS 마커를 대체할 수 있는 수단이 될 수 있다 (Muir et al, 2008). 또한 최근에는 많은 수의 genomic data 및 후성유전학적 분석 등이 개발되면서 copy number variation(CNV), methylation 변이까지도 개발 가능성 범위가 확대되고 있다 (Yi et al, 2014;Venetsky et al, 2015 (Jin et al, 2009;Hoque et al, 2013b). D-loop control region은 non-coding region으로 기능 적인 역할을 담당하지 않고 변이가 다른 영역보다 두드러지 기 때문에 많이 활용되었고, COI 유전자는 주로 조류의 품종 구분 연구에 주로 활용되어 왔다 (Hebert et al, 2003 (Cheng and Crittenden, 1994;Kaya and Yildz, 2008 (Kim et al, 2004;Cahyadi et al, 2013).…”
unclassified
“…CNVs that encompass coding regions have the potential to alter gene expression [22], with a concomitant impact on phenotypic traits. Multiple studies have already identified CNVs in diverse chicken breeds [8,11,16,[23][24][25]. Here we aimed to compare CNVs across our three lines to identify loci with the potential to contribute to phenotypic changes in commercial broilers.…”
Section: Genome Sequencing Reveals the Modern Broiler To Be Closely Rmentioning
confidence: 99%
“…To help support these programs, there is a need to identify the genetic modifications that have resulted in declined health and disease susceptibility. In attempts to meet this 4 need, several groups have employed genomic approaches to characterize a diverse set of breeds, including native Taiwanese chickens [8], experimental lines that serve as animal models [9], as well as domestic layer and broiler lines [10,11]. Aside from identifying genes that dictate physical characteristics such as plumage or skin color, these studies have identified numerous selective sweeps [8,10,12], reflecting regions with reduced heterozygosity as a consequence of positive selection.…”
Section: Introductionmentioning
confidence: 99%